Impact-sliding fretting tribocorrosion behavior of 316L stainless steel in solution with different halide concentrations - Xu Ma; Wei Tan; Remy Bonzom; Xue Mi; Guorui Zhu (Friction, 2023)
Abstract Impact-sliding caused by random vibrations between tubes and supports can affect the operation of heat exchangers. In addition, a corrosive environment can cause damage, accelerating the synergism of corrosion and wear. Therefore, the focus of this work was the impact-sliding fretting tribocorrosion behavior of 316L heat exchanger tubes at different halide concentrations. A device system incorporating the in situ electrochemical measurements of impact-sliding fretting corrosion wear was constructed, and experiments on 316L heat exchanger tubes in sodium chloride (NaCl) solution with different concentrations (0.0, 0.1, 0.5, 1.0, 3.5, and 5.0 wt%) were carried out. The synergism between wear and corrosion was also calculated and analyzed. The wear and damage mechanisms were elucidated by correlating the corrosion-wear synergism, morphologies, and material loss rates. The results indicated that the stable wear stage occurred at approximately 9–12 h, after which the corrosion current increased with the expansion of the wear area. As the halide concentration increased, the scale of damage on the wear scars gradually decreased, changing from being dominated by cracks, delaminations, and grooves to being dominated by scratches, microgrooves, and holes. There was an obvious positive synergism between wear and corrosion. The material loss was dominated by pure mechanical wear and wear enhanced by corrosion, but corrosion enhanced by wear contributed more than tangential sliding fretting corrosion. The total mass loss increased gradually in the range of 0.0–0.5 wt% and decreased in the range of 0.5–5.0 wt%. Large-scale damage enhanced by corrosivity and small-scale damage reduced by lubricity dominated the material loss at low and high concentrations, respectively.